Exploring the interplay between undergraduates' perception of Islamic communication ethics and their practice in assertive communication - Abdul Majid, Nurulhikmah; Abdullah, Nur Nabilah; Ramdzan Ali, Al Amirul Eimer; Ramli, Mohd Safwan; Ayob, Nur Hidayah (Human Resource Management Academic Research Society (HRMARS), 2024)
Assertive communication, which involves expressing one's demands while respecting others, aligns with the ideals of Islamic communication ethics. While there are similarities, current research must establish a comprehensive connection between these concepts. Previous studies have primarily focused on assertive communication from a Western standpoint, disregarding the valuable perspectives that Islamic ethical principles can provide. Further study is required to investigate the correlation between assertive communication and Islamic communication ethics. This study aims to address this gap by quantitatively analysing Islamic communication ethics practices and assertive communication among Muslim students. Data was collected from 100 participants at an International Islamic University in Malaysia through a questionnaire method. A statistical research showed that there was a correlation between how undergraduate students see Islamic communication ethics and their use of assertive communication. The results emphasise the relevance of integrating Islamic communication ethics into assertive communication, emphasising the centrality of ethical factors in interpersonal relationships.